Legal Policy in the Prevention of Narcotics in Indonesia - Muhammad Yunus Idy; Marif; Handar Subhandi Bakhtiar (Institute of Medico-legal Publications Pvt Ltd, 2021)
The purpose of law enforcement against criminal acts of narcotics and psychotropic abuse is to improvethe health status and human resources of Indonesia. The new law concerning narcotics has two approachesto parties using narcotics illegally or in other words, abusing narcotics. The first approach is to see thedrug users as victims so that they must be rehabilitated, and the second approach is to look at drug users asperpetrators of criminal acts. Criminal acts related to narcotics crimes can generally be divided into 3 (three)types, namely supplying which is usually done by producers or importers, The act of distributing narcoticsand other illegal drugs carried out by dealers or sellers and then the users or people who abuse the narcotics.Therefore, the efforts to eradicate narcotics abuse must include all those three types of activities or actions.The efforts to eradicate it must start from the upstream part of the supplier.The policy in combating narcoticsabuse is a positive legal policy which is not only merely the implementation of normative juridical laws, butalso requires a factual juridical approach that is comprehensive and integral.